The effect of acupuncture therapy on glycemic control in type 2 diabetes mellitus (Xiao Ke) patients with Kidney Yin Deficiency Syndrome - Chandra, Chandra; Rosyida, Muslihatin Khuril; Nando, Aryaprana; Xaverius, Franciscus (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2026)
A metabolic disorder known as diabetes mellitus (DM) causes hyperglycemia, or abnormally high blood sugar levels, as a result of insulin resistance or insufficiency. This quantitative research was designed to find out how acupuncture treatment affects blood sugar levels in individuals with kidney yin deficiency syndrome and type 2 diabetes (Xiāo KĔ). Bekasi, West Java, was the site of the research, which lasted from March to June of 2025. A purposive sample strategy was used to select a total of 20 individuals, all of whom were 20 to 30 years old. Women made up a larger proportion of the individuals (65%) than males (35%), and the average age was 27 (the median). Employers made up 25% of the sample, while housewives accounted for 20%. The majority of participants were self-employed at 55%. The subjects had daily acupuncture treatments for a duration of six days. Prior to and during the intervention, blood sugar levels were monitored. A blood sugar level of 136.25 mg/dl was typical before the intervention, with a range of 128 to 142 mg/dl. The average dropped to 115.80 mg/dl after the intervention, with a range of 110–121 mg/dl. The average drop in blood sugar levels was 17.94%, or 24.45 mg/dl. In one study, 15% of participants had a reduction of 23 mg/dl. With a result greater than 0.05, the Shapiro-Wilk normalcy test confirmed that the data followed a normal distribution. A statistically significant difference was seen between sugar levels before and during medication, as shown by the paired sample t-test findings (sig. (2-tailed) value of 0.000 < 0.05). Research in individuals with type 2 diabetes and kidney yin deficiency syndrome found that acupuncture treatment significantly reduced blood sugar levels.